Implementasi Sistem Akuaponik Ikan–Sayuran untuk Penguatan Ketahanan Pangan Berbasis Pesantren - Endang Sri Utami; M. Hadziq Qulubi; Titin Liana Febriyanti (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This Community Service (PkM) activity aims to implement a fish-vegetable aquaponics system to strengthen pesantren-based food security at the Minhajur Rufaqo’ Islamic Boarding School in East Lampung. Implementation methods include empowerment, technology transfer, and strengthening sustainability through outreach, training, system installation, maintenance, as well as mentoring and evaluation. The aquaponics system integrates tilapia (Oreochromis niloticus) and water spinach (Ipomoea aquatica) cultivation with recirculating aquaculture system (RAS) technology. The results of the activity show that all members of the pesantren actively participated and experienced an increase in knowledge and skills in aquaponics management. The constructed system functioned well, as evidenced by a fish survival rate of 87% and optimal water spinach growth. Operational challenges were identified during monitoring activities but were subsequently addressed through schedule adjustments and the use of checklists. This program demonstrates that aquaponics is an effective water- and land-efficient cultivation technology that supports self-reliance and sustainable food security within the pesantren environment.